IN VITRO ANTIMICROBIAL ACTIVITY SCREENING OF XYLARIA HYPOXYLON - Canli, Kerem; Akata, Ilgaz; Altuner, Ergin Murat (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Fungi have a potential of using both as nutritive and medicinal food stuff. Because of containing several therapeutic agents, they are reported to be used for hundreds of years to treat several diseases caused by bacteria, fungi, viruses and parasites. The aim of this study is to determine the in vitro antimicrobial activity of Xylaria hypoxylon, which were collected from Yomra, Trabzon, Turkey. Materials and Methods: X. hypoxylon samples were air dried and extracted by using ethanol. Antimicrobial activity of X. hypoxylon ethanol extracts were investigated against 21 bacterial and 2 fungal strains, namely, Bacillus subtilis DSMZ 1971, Bacillus subtilis ATCC 6633, Candida albicans ATCC 10231, Candida albicans DSMZ 1386, Enterobacter aerogenes ATCC 13048, Enterococcus durans, Enterococcus faecalis ATCC 29212, Enterococcus faecium, Escherichia coli ATCC 25922, Escherichia coli CFAI, Klebsiella pneumoniae, Listeria innocula, Listeria monocytogenes ATCC 7644, Pseudomonas aeruginosa DSMZ 50071, Pseudomonas fluorescence P1, Salmonella enteritidis ATCC 13075, Salmonella infantis, Salmonella kentucky, Salmonella typhimurium SL 1344, Staphylococcus aureus ATCC 25923, Staphylococcus carnosus MC1.B, Staphylococcus epidermidis DSMZ 20044 and Streptococcus agalactiae DSMZ 6784 by using the disk diffusion method. Results: It is observed that ethanol extracts of X. hypoxylon has antimicrobial activity against several Gram positive and Gram negative microorganisms tested. As a result of the study, an antimicrobial activity of X. hypoxylon found against most of strains used in the study. Conclusion: The results of our study clearly puts forward that X. hypoxylon could have a possible medicinal use.